Regulatory Mechanisms and Pathophysiological Significance of IP3 Receptors and Ryanodine Receptors in Drug Dependence - Koji Mizuno; Kazuhiro Kurokawa; Seitaro Ohkuma (Elsevier, 2013)
Calcium is a ubiquitous intracellular signaling molecule required for initiating and regulating neuronal functions. Ca2+ release from intracellular stores in the endoplasmic reticulum into intracellular spaces via intracellular Ca2+-releasing channels, inositol 1,4,5-trisphosphate receptors (IP3Rs) and ryanodine receptors (RyRs), is one mechanism altering the intracellular Ca2+ concentration. Functional abnormalities in endoplasmic calcium channels can disturb cellular calcium homeostasis and, in turn, produce pathological conditions. Indeed, our recent studies have indicated the involvement of these upregulated calcium channels in development of the rewarding effect of a drug of abuse and the suppression of its rewarding effect by calcium-channel inhibitors, which suggests a possible functional relationship between intracellular dynamics and the development of the rewarding effects induced by an abused drug. Although previous reports showed that the most important regulators of both RyR and IP3R channel functions are changes in the intracellular Ca2+ concentration and in phosphorylation of these channels by numerous kinases and calcium modulators, little information is available to clarify how the expression of intracellular calcium channels is regulated. In this review, we therefore introduce the roles and regulatory mechanisms of intracellular calcium channels in drug dependence, especially in the rewarding effect induced by the abused drug. Keywords:: drug dependence, type 1 inositol 1,4,5-trisphosphate receptors, AP-1, nuclear factor of activated T-cells c4 (NFATc4), calcium channel